Question Number 14444 by tawa tawa last updated on 31/May/17
$$\mathrm{Solve}\:\mathrm{the}\:\mathrm{differential}\:\mathrm{equation}\: \\ $$$$\mathrm{y}'\:=\:\frac{\mathrm{2x}\:+\:\mathrm{3y}\:−\:\mathrm{4}}{\mathrm{4x}\:+\:\mathrm{3y}\:+\:\mathrm{2}} \\ $$
Answered by mrW1 last updated on 31/May/17
$${let}\:{x}={u}+{p}\:{and}\:{y}={v}+{q} \\ $$$$\mathrm{2}{x}+\mathrm{3}{y}−\mathrm{4}=\mathrm{2}{u}+\mathrm{3}{v}+\mathrm{2}{p}+\mathrm{3}{q}−\mathrm{4} \\ $$$$\mathrm{4}{x}+\mathrm{3}{y}+\mathrm{2}=\mathrm{4}{u}+\mathrm{3}{v}+\mathrm{4}{p}+\mathrm{3}{q}+\mathrm{2} \\ $$$${let} \\ $$$$\mathrm{2}{p}+\mathrm{3}{q}−\mathrm{4}=\mathrm{0}\:\:\:…\left({i}\right) \\ $$$$\mathrm{4}{p}+\mathrm{3}{q}+\mathrm{2}=\mathrm{0}\:\:\:…\left({ii}\right) \\ $$$$\left({ii}\right)−\left({i}\right): \\ $$$$\mathrm{2}{p}+\mathrm{6}=\mathrm{0} \\ $$$$\Rightarrow{p}=−\mathrm{3} \\ $$$$\mathrm{2}\left({i}\right)−\left({ii}\right): \\ $$$$\mathrm{3}{q}−\mathrm{10}=\mathrm{0} \\ $$$$\Rightarrow{q}=\frac{\mathrm{10}}{\mathrm{3}} \\ $$$$\Rightarrow{x}={u}−\mathrm{3} \\ $$$$\Rightarrow{y}={v}+\frac{\mathrm{10}}{\mathrm{3}} \\ $$$${dx}={du} \\ $$$${dy}={dv} \\ $$$$\Rightarrow\frac{{dv}}{{du}}=\frac{\mathrm{2}{u}+\mathrm{3}{v}}{\mathrm{4}{u}+\mathrm{3}{v}} \\ $$$${let}\:{v}={tu} \\ $$$$\frac{{dv}}{{du}}={t}+{u}\frac{{dt}}{{du}} \\ $$$$\Rightarrow{t}+{u}\frac{{dt}}{{du}}=\frac{\mathrm{2}+\mathrm{3}{t}}{\mathrm{4}+\mathrm{3}{t}} \\ $$$${u}\frac{{dt}}{{du}}=\frac{\mathrm{2}+\mathrm{3}{t}}{\mathrm{4}+\mathrm{3}{t}}−{t}=−\frac{\mathrm{3}{t}^{\mathrm{2}} −{t}−\mathrm{2}}{\mathrm{4}+\mathrm{3}{t}}=−\frac{\left(\mathrm{3}{t}+\mathrm{2}\right)\left({t}−\mathrm{1}\right)}{\mathrm{3}{t}+\mathrm{4}} \\ $$$$\frac{\mathrm{3}{t}+\mathrm{4}}{\left(\mathrm{3}{t}+\mathrm{2}\right)\left({t}−\mathrm{1}\right)}{dt}=−\frac{{du}}{{u}} \\ $$$$\frac{\mathrm{3}{t}+\mathrm{2}+\mathrm{2}}{\left(\mathrm{3}{t}+\mathrm{2}\right)\left({t}−\mathrm{1}\right)}{dt}=−\frac{{du}}{{u}} \\ $$$$\left[\frac{\mathrm{3}}{\mathrm{5}}\left(\frac{\mathrm{1}}{{t}−\mathrm{1}}\right)−\frac{\mathrm{6}}{\mathrm{5}}\left(\frac{\mathrm{1}}{\mathrm{3}{t}+\mathrm{2}}\right)\right]{dt}=−\frac{{du}}{{u}} \\ $$$$\int\left[\frac{\mathrm{3}}{\mathrm{5}}\left(\frac{\mathrm{1}}{{t}−\mathrm{1}}\right)−\frac{\mathrm{6}}{\mathrm{5}}\left(\frac{\mathrm{1}}{\mathrm{3}{t}+\mathrm{2}}\right)\right]{dt}=−\int\frac{{du}}{{u}} \\ $$$$\frac{\mathrm{3}}{\mathrm{5}}\int\frac{\mathrm{1}}{{t}−\mathrm{1}}\:{dt}−\frac{\mathrm{6}}{\mathrm{5}}\int\frac{\mathrm{1}}{\mathrm{3}{t}+\mathrm{2}}\:{dt}=−\int\frac{{du}}{{u}} \\ $$$$\frac{\mathrm{3}}{\mathrm{5}}\mathrm{ln}\:\left({t}−\mathrm{1}\right)−\frac{\mathrm{18}}{\mathrm{5}}\mathrm{ln}\:\left(\mathrm{3}{t}+\mathrm{2}\right)=−\mathrm{ln}\:{u}+{C}_{\mathrm{1}} \\ $$$$\frac{\mathrm{3}}{\mathrm{5}}\mathrm{ln}\:\left(\frac{{v}}{{u}}−\mathrm{1}\right)−\frac{\mathrm{18}}{\mathrm{5}}\mathrm{ln}\:\left(\frac{\mathrm{3}{v}}{{u}}+\mathrm{2}\right)=−\mathrm{ln}\:{u}+{C}_{\mathrm{1}} \\ $$$$\frac{\mathrm{3}}{\mathrm{5}}\mathrm{ln}\:\left(\frac{{y}−\frac{\mathrm{10}}{\mathrm{3}}}{{x}+\mathrm{3}}−\mathrm{1}\right)−\frac{\mathrm{18}}{\mathrm{5}}\mathrm{ln}\:\left(\frac{\mathrm{3}{y}−\mathrm{10}}{{x}+\mathrm{3}}+\mathrm{2}\right)=−\mathrm{ln}\:\left({x}+\mathrm{3}\right)+{C}_{\mathrm{1}} \\ $$$$\frac{\mathrm{3}}{\mathrm{5}}\mathrm{ln}\:\left(\frac{{y}−{x}−\mathrm{3}}{{x}+\mathrm{3}}\right)−\frac{\mathrm{18}}{\mathrm{5}}\mathrm{ln}\:\left(\frac{\mathrm{3}{y}+\mathrm{2}{x}−\mathrm{4}}{{x}+\mathrm{3}}\right)=−\mathrm{ln}\:\left({x}+\mathrm{3}\right)+{C}_{\mathrm{1}} \\ $$$$\mathrm{3ln}\:\left(\frac{{y}−{x}−\mathrm{3}}{{x}+\mathrm{3}}\right)+\mathrm{5ln}\:\left({x}+\mathrm{3}\right)−\mathrm{18ln}\:\left(\frac{\mathrm{3}{y}+\mathrm{2}{x}−\mathrm{4}}{{x}+\mathrm{3}}\right)={C} \\ $$$$\mathrm{3ln}\:\left({y}−{x}−\mathrm{3}\right)+\mathrm{20ln}\:\left({x}+\mathrm{3}\right)−\mathrm{18ln}\:\left(\mathrm{3}{y}+\mathrm{2}{x}−\mathrm{4}\right)={C} \\ $$$${or} \\ $$$$\frac{\left({y}−{x}−\mathrm{3}\right)^{\mathrm{3}} \left({x}+\mathrm{3}\right)^{\mathrm{20}} }{\left(\mathrm{3}{y}+\mathrm{2}{x}−\mathrm{4}\right)^{\mathrm{18}} }={C} \\ $$
Commented by tawa tawa last updated on 31/May/17
$$\mathrm{God}\:\mathrm{bless}\:\mathrm{you}\:\mathrm{sir}.\:\mathrm{I}\:\mathrm{really}\:\mathrm{appreciate}\:\mathrm{your}\:\mathrm{effort}. \\ $$